2015
DOI: 10.1039/c5sc01421b
|View full text |Cite
|
Sign up to set email alerts
|

In situ investigation of dissociation and migration phenomena at the Pt/electrolyte interface of an electrochemical cell

Abstract: Using near ambient pressure X-ray photoelectron spectroscopy we probe in situ the double layer at the Pt/liquid electrolyte interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
0
31
0
1
Order By: Relevance
“…Moving towards realistic operating conditions, Arrigo et al recently studied Pt nanoparticles deposited on an acidic-polymer membrane using ambient pressure X-ray photoelectron spectroscopy (APXPS) in a humidied (solid/gas interface) environment. 27 The authors found that the rst stage of Pt oxidation involves the formation of a surface Pt oxide 27,33 where atomic oxygen (O) is weakly bound to Pt (Pt-O).…”
Section: Introductionmentioning
confidence: 99%
“…Moving towards realistic operating conditions, Arrigo et al recently studied Pt nanoparticles deposited on an acidic-polymer membrane using ambient pressure X-ray photoelectron spectroscopy (APXPS) in a humidied (solid/gas interface) environment. 27 The authors found that the rst stage of Pt oxidation involves the formation of a surface Pt oxide 27,33 where atomic oxygen (O) is weakly bound to Pt (Pt-O).…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances, nearly all in situ studies of energyrelated materials have been performed using bulk sensitive spectroscopies, such as hard X-ray XAS and XRD. The recent coupling of operational systems with surface sensitive techniques, such as X-ray photoelectron spectroscopy (XPS), provides significant opportunity for shedding new light on phenomena occurring at the solid/liquid electrified interface (38,39,40,41,42,43,44,45,46,47,48). In this work, we study, under operando conditions, the chemical and structural evolution of different conformal CoO x catalyst layers formed by plasma-enhanced atomic layer deposition (PE-ALD) on p + -Si substrates (37) as a function of the applied electrochemical potential.…”
mentioning
confidence: 99%
“…[40,41], but to the best of our knowledge have not been considered so far in the context of ORR by Pt catalysts. Our study will be divided into two parts: The main body of this work, Section 3.a, employs an implicit representation of the water solvent, allowing us to investigate in detail all the steps of the ORR.…”
Section: Resultsmentioning
confidence: 99%